Estimation of aerosol absorption under summer conditions of Western Siberia from sun photometer data - Bedareva, T. V.; Zhuravleva, T. B. (Atmospheric and oceanic optics, 2012)
We tested the methods for retrieving the aerosol single scattering albedo and scattering phase function (asymmetry factor), developed by the authors earlier, from measurements of clear-sky radiance in the solar almucantar at the Tomsk station of the AERONET photometric network in 2003–2009. It is shown that, under conditions of strong atmospheric turbidity (fires), the results obtained using the suggested approach and the Dubovik-King algorithm agree well. Under typical summer conditions of Western Siberia, the average single scattering albedo in the blue and green wavelength regions are ∼0.90–0.92 and close to those presented in the WCP and OPAC models for continental aerosol.